Social work and poverty reduction in Southern Africa: The case of Eswatini, Lesotho, and Zimbabwe - Jotham Dhemba; Tatenda Goodman Nhapi (Social Work & Society, 2020)
The interactions of history, geography, domestic policies, and geopolitics have contributed to the chronic and pervasive poverty that many African countries find themselves in. The unrelenting HIV and AIDS pandemic and as of 2020, COVID 19 pandemic, has devastated the social fabric, and older persons, women, children, and youths, and people with disabilities are among the most impoverished. Poverty alleviation has been deeply intertwined with social work's endeavors to enhance people's social functioning. Moreover, social workers have an ethical responsibility to assist the poor and marginalized in society (Dhemba 2012b). Social work is, therefore, a welfare profession with a concern for social justice and human wellbeing, consequently, given that the primary concern of the majority of social work service users is poverty (Twikirize, Spitzer, Wairire, Mabeyo, and Rutikanga (2014). Nonetheless, the relevance and effectiveness of social work depends on its ability to address the endemic poverty, which is the root cause of most social problems. Poverty reduction and its eventual eradication are therefore, the sine qua non of social work education and practice which is why many African countries have shifted from welfare to a developmental focus. To this end, some countries on the African continent have renamed their public welfare ministries to ministries or departments of social development. In the same vein, the social work curriculum at many Universities in Southern Africa, including Eswatini, Lesotho, and Zimbabwe have social development as one of the core courses.  This article examines social work education, training, and practice in Southern Africa, focusing on Eswatini (formerly Swaziland), Lesotho, and Zimbabwe. The article interrogates the social work curriculum's responsiveness and fitness of practitioners to address the pervasive poverty in these countries. The article is grounded on the developmental social work approach as advocated by proponents such as Gray (2017), Mupedziswa (2001), and Midgley (2010), amongst other scholars. This article's methodology is framed on a review of the social work curriculum and research and policy documents on poverty in Southern Africa. Furthermore, the article offers pathways on how to embed poverty mitigation in social work education and practice. This is particularly important in guiding interventions for the realisation of the Global Social Work Agenda's desired outcomes.